2014
DOI: 10.3163/1536-5050.102.4.007
|View full text |Cite
|
Sign up to set email alerts
|

Health sciences librarians' awareness and assessment of the Medical Library Association Code of Ethics for Health Sciences Librarianship: the results of a membership survey

Abstract: Comments provided by respondents who disagreed with the majority views suggest that the MLA code could usefully include a supplementary guide with practical advice on how to reason through a number of ethically challenging situations that are typically encountered by health sciences librarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Periodically emphasizing MLA's code is warranted, as the survey results mentioned above indicated that 13.5% of the respondents did not know the code even exists [12]. Health sciences librarians continue to be confronted with the same kinds of ethical situations that we have always faced, in addition to some new ones related to technology and research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodically emphasizing MLA's code is warranted, as the survey results mentioned above indicated that 13.5% of the respondents did not know the code even exists [12]. Health sciences librarians continue to be confronted with the same kinds of ethical situations that we have always faced, in addition to some new ones related to technology and research.…”
Section: Resultsmentioning
confidence: 99%
“…Task force survey results reported in this issue of the JMLA indicate that some respondents would like to see examples of how the code can be applied to specific situa tions [12]. Task force survey results reported in this issue of the JMLA indicate that some respondents would like to see examples of how the code can be applied to specific situa tions [12].…”
Section: The Futurementioning
confidence: 99%
“…Many of these framing practices fall within the Medical Library Association (MLA) and Canadian Health Library Association (CHLA) code of ethics where librarians are asked to ensure ‘that the best available information is provided to the client’, a principle that is not further explained by MLA or CHLA *. In a recent survey about MLA members’ knowledge of the MLA code of ethics, Byrd, Devine and Corcoran discussed how 46.6 per cent of the survey respondents thought that the MLA code about ‘best available information’ was ‘more important’ than others, but some also responded that this code was ‘particularly challenging to follow in their professional activities’. In the present study, participants also were conflicted about what constituted the best evidence, as some relied heavily on narrow, evidence‐based notions of evidence quality (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…With twice as many statements as the average in the other 7 codes (20 vs. 9.7), the AMIA code specifies a larger number of all the norms in our framework (14), and it specifies the largest number of behavioral norms with 2 or more statements (7). However, the ML A and ALA codes also specify a proportionately large number of behavioral norms (13 and 12, respectively).…”
Section: Overall Pattern Of Principle and Norm Specificationsmentioning
confidence: 97%
“…One study focused on librarians working in health care or research settings [6], and another focused on member perceptions of the Medical Library Association (MLA) Code of Ethics for Health Sciences Librarianship [7]. Although the values specified in these studies were based on the particular context of each profession, the biomedical framework of Beauchamp and Childress's principles and norms still held up well.…”
Section: A Brief Review Of the Recent Biomedical Library And Informmentioning
confidence: 99%